2011
DOI: 10.1007/s00198-011-1685-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influence on bone mineral density in Korean twins and families: the healthy twin study

Abstract: The high heritability of BMD in this Korean population similar to those found in Western populations and the significant common genetic basis between BMDs at different sites strongly supports a significant role of genetic determinants on the risk of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
(90 reference statements)
0
14
2
1
Order By: Relevance
“…Whereas Korean males showed the highest heritability (0.76) in lumbar BMD, the heritability of lumbar BMD (0.66) was relatively low compared to pelvic BMD (0.78) in females 53 . We cannot exactly understand the reason for and clinical significance of this finding.…”
Section: Discussionmentioning
confidence: 87%
“…Whereas Korean males showed the highest heritability (0.76) in lumbar BMD, the heritability of lumbar BMD (0.66) was relatively low compared to pelvic BMD (0.78) in females 53 . We cannot exactly understand the reason for and clinical significance of this finding.…”
Section: Discussionmentioning
confidence: 87%
“…Quando utilizado o DXA, são encontrados resultados semelhantes, havendo maior correlação da DMO entre os gêmeos monozigóticos e menor correlação entre pais e filhos, demonstrando que 51-76% da variação na DMO é hereditária 39. Mais estudos são necessários em relação aos fatores genéticos, uma vez que as pesquisas com esse enfoque demonstraram haver afinidade genética em relação à massa óssea em gêmeos monozigóticos e dizigóticos, com diferenças preditas pelas variáveis antropométricas.…”
Section: Genéticaunclassified
“…This disease accounts for approximately 1.5 million new fracture cases each year, representing a huge economic burden on health care systems, with annual costs estimated to be $17 billion in the United States alone and expected to rise 50% by the year 2025 1 , 2 . Osteoporosis is mainly characterized by bone fragility (most individuals have a low BMD) and it is a highly heritable trait with heritability ranging from 0.5 to 0.8 3 . Recent studies have shown that multiple genetic variants in Wnt pathway components including AXIN1 , CTNNB1 , DKK1 , LRP4 , LRP5 , MEF2C , RSPO3 , SFRP4 , SOST , WLS , WNT3 , WNT4 , WNT5B and WNT16 are associated with BMD 4 11 .…”
Section: Introductionmentioning
confidence: 99%